Migration and Gender Health: Navigating Intersecting Vulnerabilities and Resilience: A case study of Lahore - Zaheer, Ifra (Symbiohealth, 2025)
This qualitative study investigates the gendered health impacts of internal migration on women in Lahore, Pakistan, through in-depth interviews with ten female migrants. Employing a phenomenological approach and thematic analysis, the research explores how the migration process from pre-departure motivations through transit to urban settlement shapes physical, mental, and social well-being through an intersectional lens. The findings reveal that migration is a deeply gendered experience driven by economic precarity and shaped by gendered pressures. Participants reported significant vulnerabilities, including fear of harassment during transit, precarious living conditions in informal settlements, and formidable barriers to healthcare characterized by financial cost (mehngai) and systemic disrespect (be-izzati). These intersecting vulnerabilities of gender, poverty, and rural origin manifested in starkly gendered health outcomes, most notably a high, yet unaddressed, burden of mental distress and severely limited access to reproductive healthcare. However, the study also uncovers profound resilience, as women actively navigated these challenges through the formation of "jhuggi networks" informal community support systems that provided emotional, informational, and financial resources. The study concludes that effective public health interventions must be gender-transformative, addressing structural barriers while leveraging existing community resilience to bridge the gap in healthcare access for this vulnerable population.